Potential predictability of the Ethiopian summer rains: understanding local variations and their implications for water management decisions - Taye, Meron Teferi; Dyer, E.; Charles, K.J.; Hirons, L.C. (Elsevier, 2021)
Understanding the influence of large-scale oceanic and atmospheric variability on rainfall over Ethiopia has huge potential to improve seasonal forecasting and inform crucial water management decisions at local levels, where data is available at appropriate scales for decision makers. In this study, drivers of Ethiopia‘s main rainy season, July-September (JAS), are investigated using correlation analysis with sea surface temperature (SST). The analysis showed local spatial variations in the drivers of JAS rainfall. Moreover, the analysis revealed strong correlation between March to May (MAM) SST and JAS rainfall in particular regions. In addition to the influence of SSTs, we highlighted one of the mechanisms explaining the regional pattern of SST influence on Ethiopian rainfall, the East African Low-Level Jet. Moreover, examining the occurrence of large-scale phenomena provided additional information, with very strong ENSO and positive IOD events associated with drier conditions in most part of Ethiopia. A sub-national analysis, focused at a scale relevant for water managers, on the Awash basin, highlighted two distinct climate zones with different relationships to SSTs. June was not included as part of the rainy season as in some areas June is a hot, dry month between rainy seasons and in others it can be used to update sub-seasonal forecasts with lead time of one month for JAS rainfall. This highlights the importance of understanding locally relevant climate systems and ensuing sub-seasonal to seasonal forecasts are done at the appropriate scale for water management in the complex topography and climatology of Ethiopia.